Penggunaan media pembelajaran wordwall untuk meningkatkan minat dan motivasi belajar siswa pada pembelajaran IPA di Sekolah Dasar - Pradani, Tatsa Galuh (ARKA INSTITUTE, 2022)
The covid pandemic has forced educational institutions in Indonesia to conduct offline learning online using wordwall media to help students understand the material in science learning during the covid 19 pandemic. The method used in this research is qualitative. The target of this activity is 20 fourth grade students. The results showed that there was a change in attitude that occurred in students after learning by using wordwall media. These changes can be seen from the aspect of student activity and the observation assessment criteria are measured through several indicators, including: (a) The activeness of students when participating in online teaching and learning activities as evidenced by filling in absences, (b) Student activity when collecting assignments by on time, (c) Asking about material that has not been understood. The conclusion of this study is that the use of wordwall media in the fourth grade science learning can increase students' interest and motivation in learning.